PID-Type Iterative Learning Control for Output Tracking Gearing Transmission Systems - Luong Thuy Anh; Tran Thi Thanh Nga; Vu Van Hoc (International Journal of Robotics and Control Systems, 2021)
In this paper, we propose a modified version of the Proportional Integral Derivative (PID)-type iterative learning algorithm. It is very simple to implement on a digital control device for tracking control a continuous-time system. Matlab software is used to model and simulate control algorithms. The simulative application of it to control a gearing transmission system, such that its output response follows the desired trajectory, is then carried out computationally. Obtained studying results proves that this proposed iterative learning algorithm has provided a good output tracking behavior as expected and which is robust in the sense of reducing external disturbance effects.